Overproduction of polyomavirus middle T antigen in mammalian cells through the use of an adenovirus vector. - Davidson, D (1987)
To overproduce biologically active polyomavirus middle T antigen, we used an adenovirus vector and human 293 cells as hosts. Two helper-independent recombinant adenoviruses were isolated that contain a hybrid transcription unit, in differing orientations, at a site in the adenovirus genome from which the E1a and most of the E1b transcription units have been deleted. The hybrid transcription unit consists of the adenovirus type 2 major late promoter and tripartite leader and a cDNA segment capable of encoding polyomavirus middle T antigen and accompanying 3' RNA-processing signals. Both recombinant viruses were stable and replicated to high titers in human 293 cells. The polyomavirus sequences were expressed, predominantly at late times after infection of 293 cells, to yield mRNAs that encoded middle T antigen. One of the recombinant viruses also expressed a middle T antigen-related protein in 293 cells. The latter was translated from one of several novel mRNA species that resulted from aberrant splicing and incomplete RNA processing of precursor RNA transcripts. Comparison of the amount of middle T antigen produced in 3T6 cells infected with polyomavirus with that in 293 cells infected with either of the recombinant adenoviruses, under optimal conditions for each system, revealed at least a 10-fold greater yield of the protein on a per-cell basis in the latter system than in the former. The recombinant-virus-encoded middle T antigen was biologically active, as evidenced by its ability to associate with and serve as a substrate for human pp60c-src. The functionality of the middle T antigen was further confirmed by demonstrating that both recombinant viruses efficiently transformed Rat-1 cells. These recombinant viruses will be useful to overproduce middle T antigen and to introduce the polyomavirus oncogene into a wide variety of mammalian cells.